Wideband Cylindrical Dielectric Resonator Antenna Operating in HEM11δ Mode with Improved Gain: A Study of Superstrate and Reflector Plane. (20th July 2017) - Dash, Sounik Kiran Kumar; Khan, Taimoor; Kanaujia, Binod Kumar; Nasimuddin, N.
Abstract : A wideband and high gain dielectric resonator antenna (DRA) operating in hybrid HEM11 δ mode is proposed. The investigated geometry employs one cylindrical dielectric resonator partially covered with a transparent dielectric superstrate and backed up by a single side metal coated dielectric reflector plane. The reflector is dedicated for gain enhancement while the superstrate is employed for merging of two resonant bands resulting in a single wide band. The dielectric resonator is excited by simple microstrip feed slot coupling technique and operates over X-band, ranging from 7.12 GHz to 8.29 GHz, that is, of 15.18% impedance matching bandwidth with 11.34 dBi peak gain. The different development stages like standalone DRA, DRA with superstrate, DRA with reflector, and DRA with both superstrate and reflector plane with respect to bandwidth and gain performances are analyzed properly. To the best of authors' knowledge, this is the first time this type of combination of both superstrate and reflector plane is demonstrated in DRA engineering. An antenna prototype was fabricated and characterized and a very good agreement is achieved between the simulated and measured results.